Pembinaan Keagamaan Model Gaudya Vaisnava di Pasraman Sri-Sri Nitai Gaurangga Desa Werdhi Bhuana Kecamatan Mengwi Kabupaten Badung - Supriadi, Ida Bagus Putu (Institut Hindu Dharma Denpasar, 2019)
The religious formation of the Gaudya Vaisnava model viewed from the persuasion communication strategy is very interesting to study, because the activity will describe the elements of communication whether it is effective or not. From the point of view of the communicator, for example, is it capable of applying effective message delivery techniques? in terms of communicant, does it have the characteristics to be able to understand the meaning of the message as intended by the communicator? From the message element, is the message important to be known by the communicant ?. From the media element, is the media used to convey the message effective enough? And from the element of effect, whether the similarity in meaning of messages sent and received is able to change the communicant's attitude or behavior. Thus the process of religious formation will achieve its objectives if the elements of communication work effectively.There is no research on this matter, so it is not yet known whether the religious formation of the Gaudya Waisnava model has been effective or not. For this reason, this research was specifically carried out to describe and interpret (1) how does the religious development activities of the Gaudya Vaisnava model in Pasraman Sri-Sri Nitai Gaurangga? (2) how is the function of religious formation of the Gaudya Vaisnava model in Pasraman Sri-Sri Nitai Gaurangga? And (3) what is the meaning of the religious formation of the Gaudya Vaisnava model in Pasraman Sri-Sri Nitai Gaurangga?The results of the study (1) the activities of religious formation of the Gaudya Vaisnava model include: (a) the activities of receiving students / new students; (b) the implementation of unlawful education; (c) Brahmin Diksa implementation; (d) carrying out the task of spreading the teachings of Gaudya Vaisnawa (2) the function of religious formation of the Gaudya Vaisnava model includes social functions and religious functions. Social functions encourage members to carry out their social life tasks better. Whereas the religious function encourages its members to be able to harmonize all aspects of their lives. (3) The meaning of religious formation in the Gaudya Vaisna model includes social and religious meanings. Social meaning is intended to increase the insight of its members to be more inclusive among humans. The religious meaning is intended to increase the insight of its members in order to be able to harmonize all their life activities.